Characterization of the solvent extractable organic compounds in PM2.5 aerosols in Hong Kong - Mei* Zheng; Ming Fang; Fu Wang; K.L To (Atmospheric Environment, 2000)
The results from a year-long monthly study of the solvent extractable organic compounds (SEOC) in PM2.5 of the ambient aerosols in Hong Kong are reported. A total of 18 samples were analyzed. The extracted organic compounds were separated into four major fractions (n-alkanes, fatty acids, alkanols and PAHs (polycyclic aromatic hydrocarbons)) and identified with GC-MS (gas chromatography–mass spectrometry). The percentage of each fraction in total yield is as follows: fatty acids at 46–80%, alkanes at 10–34%, alkanols at 4–21%, and PAHs at 1–6%. Compared to the TSP (total suspended particulates) samples from our previous studies, the PAH fraction was higher in PM2.5 than TSP (0.5–2.5%). The bias of PAHs in PM2.5 suggests potential implications in health impact because PM2.5 is respirable. The total yield (defined as the sum of the four fractions) in PM2.5 was in the range of 56.4–233.6ngm−3. The sources of SEOC in PM2.5 could be attributed to vehicular, biogenic and microbial origins. On the average, 79% of the alkanes in PM2.5 came from vehicular emissions. U:R (ratio of unresolved to resolved components), an index to assess the magnitude of petroleum residues in aerosols, exhibited higher values in PM2.5 (average 3.2, range 1.0–5.9) than TSP (average 2.4, range 1.1–3.3). CPI (carbon preference index) of alkanes showed an inverse relationship with U:R, and a positive correlation with the percentage of alkanes from higher plant wax. Although U:R and CPI have been widely used as indices in source apportionment, their effectiveness was demonstrated for the first time from the statistical point of view in this paper. It was discovered that the CPI=1 (a characteristic of petroleum hydrocarbons) envelope and Cmax shifted towards lower carbon numbers in winter, suggesting there was more contribution from vehicular emission. PAHs had the following range 0.7–12.2ngm−3. The positive correlation with benzo(ghi)perylene suggested that they were of vehicular origin. Distinct seasonal variation in PAH concentration was found with higher concentrations in the winter samples. The concentration range of fatty acids in PM2.5 (31.1–168.8ngm−3) indicated that the microbial contribution in the PM2.5 samples was systematically lower in late fall and winter (average 52%) while larger in the hotter weather (over 80%), suggesting higher microbial activities in the summer. A ratio as high as 1.93 in summer for C18:1/C18:0 and only 0.69 in winter suggested that there were more aged aerosols in winter while more fresh emissions were found in summer. The results of SEOC in the PM2.5 aerosols indicated that vehicular emission was the characteristic of Hong Kong's aerosols.
Keywords: Hong Kong